Why use ROSCAs when you can use banks? Theory and evidence from Ethiopia - Abbi M. Kedir; Richard Disney; Indraneel Dasgupta (Institute for the Study of Labor (IZA), 2011)
Much of the existing literature on the use of informal credit arrangements such as ROSCAs (Rotating and Credit Saving Associations) theorises the use of such institutions as arising from market failures in the development of formal saving and credit mechanisms. As economic development proceeds, formal institutions might therefore be expected to displace ROSCAs. We show, using household data for Ethiopia, that in fact use of formal institutions and ROSCAs can co-exist, even in the same household. We examine usage of both formal and informal institutions across the household income gradient, and provide a theoretical model consistent with these empirical facts.
urn:nbn:de:101:1-20110621262
Keywords: O16; O17; 330; household saving; credit institutions; ROSCAs; Ethiopia